Exploring the relationship between an "English-only" language-in-education policy and bilingual practices in secondary schools in Zanzibar - Maalim, Haroun Ayoub (Rhodes University, Faculty of Humanities, School of Languages, 2015)
This thesis reports on the relationship between an English-only language-ineducation policy and bilingual practices in secondary schools in Zanzibar. The focus is on language use in the classroom against the backdrop of a top-down and English-only language-in-education policy. The main purpose has been to gain an in-depth understanding of the relationship between the stipulations of the policy which was imposed from above and the judicious bilingual practices which are a commonly accepted as the norm in secondary schools in Zanzibar. The study employed a mixed method approach (QUAL+quant) and embraced elements of ethnography. The data for this study was gathered from two secondary schools which were purposively selected on the basis of parameters that were set in this study. Among other things, these include the secondary schools which have both 'Ordinary level' and 'Advance level', and the schools which teach the same subject using Kiswahili as the language of learning and teaching at one level, and English as the language of learning and teaching at another level. Data were obtained from multiple sources. On the one hand, through ethnography, classroom observations, semi-structured interviews and focus group discussions with teachers and students, and interviews with key actors were conducted. On the other hand, students' test scripts, and students' test and examination results (scores) were analysed. Both purposive and random sampling were used to get the participants. Drawing from Ruiz's (1984) seminal tripartite orientations of language planning (language as right, language as problem, and language as resource) thematic analysis, content analysis, and the Statistical Package for the Social Sciences (SPSS) were used to analyse data. The findings reveal that the use of bilingual (English and Kiswahili) in English medium subjects is a resource rather than a deficit since an overwhelming majority of students and some teachers cannot function positively in the topdown English-only language-in-education policy. Most significantly, teachers use Kiswahili in English medium subjects as a strategy for teaching terminologies, abstract concepts, and unfamiliar topics, as well as for clarification of ideas and for comprehension check. The study further indicates that the examinations and tests of English medium subjects do not assess what is exactly intended to be assessed (subject matter), but instead they assess English language. In addition, empirical evidence shows that language is a factor for students' achievements in that students performed considerably better when the subjects were assessed in Kiswahili compared to the same subjects assessed in English. The findings further reveal that Kiswahili is suitable to be used as a sole language of learning and teaching in secondary schools of Zanzibar. Based on these findings, the study recommends that the use of Kiswahili in English medium subjects should be officially recognised and students should be given options of the language of assessment as an urgent step. Furthermore, given the urgency of the need for improving students' performance, it is now high time to introduce Kiswahili medium of instruction secondary schools in Zanzibar which should co-exist with English medium of instruction secondary schools.
Keywords: Language and education -- Zanzibar; Native language and education -- Zanzibar; Code switching (Linguistics) -- Zanzibar; Language policy -- Zanzibar